Absorption, tissue distribution, and excretion of zinc acexamate in rats - Wu Jing-Fu; Wang Min-Wei; Song Lian-Sheng; Liu Zhi-Fang (Acta Pharmacologica Sinica, 2016)
beta = 11.6 h. The bioavailability was about 52.8%. After ig [3H]ZA (4.44 MBq.kg-1), higher radioactivities were observed in kidney, liver, and gastrointestinal tract but lower in brain, fat, and femur. CONCLUSION: ZA given i.g. in rats was absorbed rapidly and distributed widely to most of the organs and tissues.